The Need to go Beyond Deterministic Data Envelopment Analysis (DEA): A Comparative Analysis with Bootstrapping DEA in Risk Management Efficiency Measurements - Zakaria, Shahsuzan (Information Management and Business Review, 2023)
This paper attempts to rectify the flaws of deterministic data envelopment analysis (DEA), induced from the characteristics of its approach. The disadvantages have drawn considerable attention in the area of banking efficiency studies, and bootstrapping DEA (BDEA) analysis has been proposed in the literature. This paper provides a comparative analysis of each approach to understand their theoretical foundations and mathematical computations, as well as their strengths and weaknesses. The arguments were empirically supported within the context of risk management efficiency analysis in banking institutions. Finally, the paper proved the need for BDEA analysis to be used while advancing measurement precision for risk management efficiency measurements.